Fish Marketing System in Nepal: Present Status and Future Prospects - Husen, Md. Akbal (International Journal of Applied Sciences and Biotechnology, 2019)
Efficient fish marketing needed for the growth of fish production as well as development of fishery sector. Domestic fish markets development in the Nepal will plays a very crucial role in the development of fisheries sector. Fish marketing system development in Nepal is in infant stage. Fish marketing channel has not been systematic in Nepal. The fish marketing infrastructure and the facilities for the fish market should be developed by identifying the possible production and collection centers in the country. Live fish have getting higher price in the market and fish imported from India price is lesser than fresh wet fish of Nepal. Government policy needed to upgrade the existing fish marketing system to ensure supply of hygiene fresh fish and processed fish for consumers. Int. J. Appl. Sci. Biotechnol. Vol 7(1): 1-5